Cultural differences in use of mobile phones by older people - Abd Malik, Sofianiza; Edwards, Alistair (IIUM Press, 2011)
In this chapter, We discussed about studies using different methods that have been conducted in twO countries (Malaysia and United Kingdom) focusing on the use of mobile technology and older people. Preliminary results suggest that there are significant statistically differences in the results which are culturally dependent